Respons Pertumbuhan Dan Produksi Bawang Merah (Allium ascalonicum L.) Terhadap Jenis Mulsa Dan Pemberian Urine Sapi - Dedy Perdata Sembiring; Rosita Sipayung; Emmy Harso Kardhinata (Jurnal Agroekoteknologi, 2016)
The aim of this research was to evaluate the influence of types of mulch and dose of cow’s urine on the growth and production of shallot. The research was conducted at the experimental field of Agricultural Faculty, North Sumatra University which about ± 25 metres above sea level, from April to July 2015. The researh was arranged by randomized block design with two factors, i.e: types of mulch (no mulch, silver black plastic, black plastic, and rice straw) and dose of cow’s urine (0, 500, 600, 700 ml/plot). Parameter observed were plant height, number of leaves per clump, number of tillers per clump, diameter of bulbs per sample, bulb fresh weight per sample, bulb dry weight per sample, bulb fresh weight per plot, and bulb dry weight per plot. The results showed that the type of mulch significantly affect to number of tillers per clump parameter at 3 weeks after planting. The aplication of cow’s urine did not give significant effect to all parameters observed.Keywords : cow’s urine, shallot, types of mulchThe aim of this research was to evaluate the influence of types of mulch and dose of cow’s urine on the growth and production of shallot. The research was conducted at the experimental field of Agricultural Faculty, North Sumatra University which about ± 25 metres above sea level, from April to July 2015. The researh was arranged by randomized block design with two factors, i.e: types of mulch (no mulch, silver black plastic, black plastic, and rice straw) and dose of cow’s urine (0, 500, 600, 700 ml/plot). Parameter observed were plant height, number of leaves per clump, number of tillers per clump, diameter of bulbs per sample, bulb fresh weight per sample, bulb dry weight per sample, bulb fresh weight per plot, and bulb dry weight per plot. The results showed that the type of mulch significantly affect to number of tillers per clump parameter at 3 weeks after planting. The aplication of cow’s urine did not give significant effect to all parameters observed.Keywords : cow’s urine, shallot, types of mulch